Gastrodin mitigates aortic valve calcification by inhibiting glycolysis and histone lactylation through interfering with valve interstitial cells - Zhang, Yu; Wang, Shunshun; Wu, Jiaqin; Du, Qianqian; Yu, Huiming; Yang, Li; Liu, Xianqiong; Xu, Kang; Wang, Chunli; Feng, Fan (Frontiers in Pharmacology, 2025)
Calcific aortic valve disease (CAVD) is the most common disease of the heart valves and is characterised by thickening, fibrosis and calcification of the aortic valve leaflets. Gastrodin, the active component of the traditional Chinese medicine Gastrodia elata Blume, has antioxidant, anti-inflammatory, anti-apoptotic and antiviral activities and is widely used in the treatment of neurological and cardiovascular diseases. Here, we report that gastrodin attenuates calcification in CAVD, but the underlying mechanism is unclear. In the present study, we investigated the molecular targets and signaling mechanisms by which gastrodin inhibits CAVD calcification. In vitro experiments such as Alizarin Red staining and In-cell western were used to evaluated the anti-calcification effect of gastrodin in the treatment of aortic valves. Transcriptome sequencing and gas chromatography-mass spectrometry analyses showed that gastrodin inhibited the glycolysis level of valvular interstitial cells (VICs). Mechanistically, gastrodin reduces the glycolysis level and lactate production of VICs by inhibiting the enzymatic activity and protein expression of PKM2. Notably, gastrodin treatment inhibited the correlation between histone lactylation H3K9la, a novel lysine-modified modality using lactate as a substrate, and the CAVD marker BMP2. The beneficial effect of gastrodin in reducing aortic valve calcification was demonstrated in vivo in high-fat fed ApoE−/− mice. In conclusion, our study shows that gastrodin exerts its anti-calcific effect by interfering with glycolysis and lactylation of VICs, demonstrating the potential of gastrodin as therapeutic agent for CAVD.